Corneal crossed links: a new alternative in the treatment of ectasia - Maygret Alberro Hernández; Janet González Sotero; Haymy Caridad Casanueva Cabezas; Eduardo Rojas Álvarez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2009)
Cross-linking a technique that allows increasing the creation of covalent links through the process of photo-oxidation among the collagen fibers and enhance the corneal biomechanical stabilization. The main objective of this procedure is to stop the development of ectasia. The indications include the Keratoconus and Pellucid Marginal Degeneration. This can reduce the necessity for permanent keratoplasty and is highly efficient in the treatment and prophylaxis of keratectasia after ablation caused by laser. Many reviewed articles prove the security and efficacy of this treatment. The confocal microscopy techniques have shown significant swelling and resistance of corneal stroma after this procedure. Density of endothelial cell and transparency of the cornea and crystallin remain unchanged. This is a simple, safe and non-invasive technique with promising results. Since this is not expensive it could be particularly useful in developing countries where corneal transplant and other procedures are very expensive.